2022
DOI: 10.3390/ma15072387
|View full text |Cite
|
Sign up to set email alerts
|

Plasma Oscillatory Pressure Sintering of Mo-9Si-8B Alloy with ZrB2 Addition

Abstract: Oscillatory pressure sintering is a novel crystal refinement technology. The doping of different concentrations of ZrB2 under oscillatory sintering technology (9 Hz) is discussed here, focusing on its macroscopic mechanics and oxidation resistance. In particular, doping 2.5 wt% ZrB2 can effectively increase the hardness of the alloy, slightly increase the fracture toughness of the alloy and have an outstanding effect on the oxidation resistance of the alloy at 1300 °C, achieving the effect of reducing mass los… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 23 publications
0
2
0
Order By: Relevance
“…Fiantok et al [ 8 ] researched a ZrB 2 thin film alloyed with Ag, and their conclusions indicated a significant improvement in ductility and tribological properties but at the cost of reduced hardness. Ding et al [ 9 ] investigated the addition of ZrB 2 into Mo-9Si-8B alloys and found that doping 2.5 wt.% ZrB 2 could obviously increase the fracture toughness of the alloy and achieve the effect of reducing mass loss by 80.3%. Guan et al [ 10 ] prepared ZrB 2 nanoparticles in an Al matrix and obtained a significant shear stress improvement (from 255 MPa to 491 MPa); meanwhile, a dislocation-strengthening effect caused by dispersed ZrB 2 particles was observed.…”
Section: Introductionmentioning
confidence: 99%
“…Fiantok et al [ 8 ] researched a ZrB 2 thin film alloyed with Ag, and their conclusions indicated a significant improvement in ductility and tribological properties but at the cost of reduced hardness. Ding et al [ 9 ] investigated the addition of ZrB 2 into Mo-9Si-8B alloys and found that doping 2.5 wt.% ZrB 2 could obviously increase the fracture toughness of the alloy and achieve the effect of reducing mass loss by 80.3%. Guan et al [ 10 ] prepared ZrB 2 nanoparticles in an Al matrix and obtained a significant shear stress improvement (from 255 MPa to 491 MPa); meanwhile, a dislocation-strengthening effect caused by dispersed ZrB 2 particles was observed.…”
Section: Introductionmentioning
confidence: 99%
“…However, porcelains have clear disadvantages, such as high brittleness and high crack growth rates, which limit their use in fields, such as mechanical washing 1 . At present, many methods have been used to overcome the brittleness issue and strengthen porcelain products, such as whisker enhancement, 2–4 dispersion enhancement, 5,6 and prestress enhancement 7,8 . Whisker enhancement and dispersion enhancement have been mainly used in the fields of advanced and traditional porcelain, whereas prestress reinforcement has commonly been applied in the fields of glass and concrete; however, in recent years, prestress reinforcement has become more widely used in the field of porcelain 9–11 …”
Section: Introductionmentioning
confidence: 99%